A Quantitative Analysis of the Nursing Students' Level of Confidence in Their Knowledge of Basic Science Concepts - Recede, Reynald Alfred A.; Ferrer, Kristel Joy; Lanot, Bernadette; Gica, Icy Jane; Andrade, Rhezia Antoinette; Isoli, Khim Nathaniel; Vitalicio , Kristine Heart; Ramos, James Aaron Marquez; Topico, Nicole Jannelza Sta. Ana; Fontanilla, Jamie Rose Curia; Quejado, Ma. Rosario; Jadaone, Aldrin; Carnecer, Rosario (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study aims to determine the first-year nursing students’ level of confidence with their knowledge in basic science concepts. A total of fifty nursing students enrolled in Pamantasan ng Lungsod ng Marikina for the academic year 2021-2022 were involved in the research. Among the participant The study aims to determine the first-year nursing students’ level of confidence with their knowledge in basic science concepts. A total of fifty nursing students enrolled in Pamantasan ng Lungsod ng Marikina for the academic year 2021-2022 were involved in the research. Among the participants, 52% (n=26) took a STEM program in Senior High School. Results revealed that the respondents are confident with their knowledge in basic science and agreed with the information associated with self-confidence. The students' confidence was influenced by the strand they took in senior high school, followed by the method of teaching used in the subject, and the experience in laboratory. Meanwhile, their monthly family income is the least important factor influencing their confidence. Therefore, nursing students, regardless of the strand they took in senior high, need more engagement in basic science concepts because it significantly contributes to their level of confidence and knowledge in nursing field. s, 52% (n=26) took a STEM program in Senior High School. Results revealed that the respondents are confident with their knowledge in basic science and agreed with the information associated with self-confidence. The students' confidence was influenced by the strand they took in senior high school, followed by the method of teaching used in the subject, and the experience in laboratory. Meanwhile, their monthly family income is the least important factor influencing their confidence. Therefore, nursing students, regardless of the strand they took in senior high, need more engagement in basic science concepts because it significantly contributes to their level of confidence and knowledge in nursing field.